(untitled) (Carte Romanze, 2019)
Starting from the study of the novel I 4 of the Decameron (the one in which an abbot forgives the lust of a young monk, because he surprised him committing the same sin), the author identifies, in the Romance literature of the Middle Ages and the Renaissance, two basic narrative models: that of the aforementioned novel ((De l’evesque qui beneï lo con; Novellino, LIV and Decameron I 4 and IX 2); and the one, in some respects similar, in which a holy man mocks the bourgeois or the peasant of whose wife he is the lover (Decameron, III 4, VII 3, IX 10; Sacchetti, Trecentonovelle, 207; Poggio Bracciolini, Liber facetiarum, 203; Masuccio, Novellino, I 3). In both models there may be the motif of the “priest’s breeches”, but in the second it acquires the tones of “mockery” that are missing in the first.